2016
DOI: 10.1890/15-1848.1
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the role of terrestrial leaves in pond food webs: a whole‐ecosystem experiment

Abstract: Terrestrial carbon and nutrients can subsidize the detrital pool of freshwater ecosystems; yet, the importance of terrestrial subsidies to lake and pond food webs is uncertain and debated. Terrestrial detritus is expected to have the greatest impact on food webs when water bodies are small and shallow with low levels of incident light. Temporary forested ponds fit this description and are often assumed to have a leaf detritus-based food web, but this has not been quantified. In a whole-ecosystem experiment, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 88 publications
1
33
0
Order By: Relevance
“…The d 13 C HC values ranged from À35& to À31& in this study (Figure 4), which was indicative of a strong reliance on autochthonous organic matter, as d 13 C of pelagic primary producers usually ranges from À36& to À25& (Vuorio, Meili, & Sarvala, 2006;Wang, Liu, Peng, & Wang, 2013). Our study thus supports the conjecture that aquatic consumers are mainly fuelled by autochthonous primary production (Holgerson, Post, & Skelly, 2016;Lau, Sundh, Vrede, Pickova, & Goedkoop, 2014;Tanentzap et al, 2017). However, relatively heavy d 13 C HC values (from À28.7 to À21.8&) were T A B L E 1 Summary of statistics for the general additive model (GAM) fitted with a Gaussian distribution to d 13 C HC values.…”
Section: Carbon Processing In Benthic Food Webs and Climate Changesupporting
confidence: 87%
“…The d 13 C HC values ranged from À35& to À31& in this study (Figure 4), which was indicative of a strong reliance on autochthonous organic matter, as d 13 C of pelagic primary producers usually ranges from À36& to À25& (Vuorio, Meili, & Sarvala, 2006;Wang, Liu, Peng, & Wang, 2013). Our study thus supports the conjecture that aquatic consumers are mainly fuelled by autochthonous primary production (Holgerson, Post, & Skelly, 2016;Lau, Sundh, Vrede, Pickova, & Goedkoop, 2014;Tanentzap et al, 2017). However, relatively heavy d 13 C HC values (from À28.7 to À21.8&) were T A B L E 1 Summary of statistics for the general additive model (GAM) fitted with a Gaussian distribution to d 13 C HC values.…”
Section: Carbon Processing In Benthic Food Webs and Climate Changesupporting
confidence: 87%
“…Consequently, while it is predicted that IRES should generally shift their trophic base from allochthonous to autochthonous sources as they dry (McIntosh et al 2017), evidence for shifts in organic matter sources supporting IRES food webs as they become more intermittent have been largely equivocal. Both algae (Bunn et al 2003, Dekar et al 2009, Holgerson et al 2016, Pettit et al 2016) and terrestrial detritus (Reid et al 2008, Leigh et al 2010, Hunt et al 2012) have been identified as key sources of the organic matter assimilated by metazoan consumers across intermittent and ephemeral freshwater habitats. Thus, the mechanisms underlying differences in the trophic base of IRES food webs might largely be accredited to differences in additional, regional ecological factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Holgerson et al. () traced the flow of 15 N‐enriched sugar maple ( Acer saccharum ) leaf litter through a single pond in a temperate forest and found that nutrients from terrestrial leaves enriched an algal‐based food web. Further, they found that most consumers relied on algae derived from litter resources instead of directly relying on litter or microbes, despite low light and net heterotrophic conditions.…”
Section: Theme 1: Evidence For the Role Of Litter As A Reciprocal Submentioning
confidence: 99%
“…Nevertheless, many small wetlands can maintain algal communities that persist under low‐light conditions (Holgerson et al. ), and it has been suggested that these algal communities are extremely important to wetland communities due to their high nutrient concentrations relative to litter inputs (Batzer et al. ).…”
Section: Theme 5: Role Of Litter Relative To Other Subsides Biotic Fmentioning
confidence: 99%